New Explicit Inflation Targeting Scheme in Peru - Castillo, Paúl (2006)
In January 2002, the Central Reserve Bank of Peru (BCRP) decided to change its monetary policy scheme, which since the beginning of the 1990s had been based on the control of monetary aggregates, for an Explicit Inflation Goals Scheme. This article analyzes the rationale for this change in the monetary regime, the particularities of its application in Peru, as it is a partially dollarized country, and its potential benefits.